2012
DOI: 10.1002/eji.201242379
|View full text |Cite
|
Sign up to set email alerts
|

GILT expression in B cells diminishes cathepsin S steady‐state protein expression and activity

Abstract: MHC class II-restricted Ag processing requires protein degradation in the endocytic pathway for the activation of CD4+ T cells. Gamma-interferon-inducible lysosomal thiol reductase (GILT) facilitates Ag processing by reducing protein disulfide bonds in this compartment. Lysosomal cysteine protease cathepsin S (CatS) contains disulfide bonds and mediates essential steps in MHC class II-restricted processing, including proteolysis of large polypeptides and cleavage of the invariant chain. We sought to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Rather as shown here, c-MYC overexpression influences cellular expression of DM, DO and GILT, critical components which modulate the efficiency of class II Ag presentation. GILT reduces disulfide bonds in Ags which allows proteins to be unfolded and further processed by acidic proteases (56, 70, 71, 87). The importance of GILT for the class II pathway has been demonstrated in GILT −/− mice which are defective in their ability to process Ag, although they express normal levels of class II (47, 88, 89).…”
Section: Discussionmentioning
confidence: 99%
“…Rather as shown here, c-MYC overexpression influences cellular expression of DM, DO and GILT, critical components which modulate the efficiency of class II Ag presentation. GILT reduces disulfide bonds in Ags which allows proteins to be unfolded and further processed by acidic proteases (56, 70, 71, 87). The importance of GILT for the class II pathway has been demonstrated in GILT −/− mice which are defective in their ability to process Ag, although they express normal levels of class II (47, 88, 89).…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, we have shown that GILT’s reductase activity facilitates the degradation of cathepsin S (Phipps-Yonas et al, 2013b). On the other hand, GILT maintains the proteolytic activity of cathepsin S (Balce et al, 2014).…”
Section: Gilt In Antigen Presentationmentioning
confidence: 99%
“…Upon translation, GILT is sorted by mannose 6-phosphate receptor pathway to endocytic compartments and finally transported into the lysosome that provides optimal low pH for its thiol reductase activity [16,17]. As the only thiol reductase in endolysosomes and phagosomes, GILT contributes to the degradation of lysosomal protease cathepsin, maintenance of cellular normal redox state and prohibition of aberrant autophagy [18][19][20][21]. GILT utilizes two cysteine residues in the CXXC reductase motif to reduce the disulphide bond of endocytosed antigens to facilitate antigen processing and presentation by MHC II and MHC-I [16,17,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%